1 Patterning the limb before and after SHH - te Welscher, P (Blackwell Science Inc, 2002)
The Summer Meeting of the Anatomical Society of Great Britain and Ireland was held at the University of Dundee, from 23rd to 25th July 2002. It included a symposium on ‘How to make a hand’. The following are abstracts of communications and posters presented at the meeting.